Systematic Approach in Precision Fertilizer Management for High Yield Rice Production in the Granary Areas of Peninsular Malaysia - Hamzah, Abdul Razak (2005)
The National Agriculture Policy 3 (NAP3) clearly stated that national-average rice yield of 7.0 t/ha has to be achieved in order to fulfill self-sufficiency level of 65% by 2010. Recently, the set yield target was revised to 10.0 t/ha by the Ministry of Agriculture and Agro-based Industry (MOA). It is a well-known fact that fertilizer is one of the major inputs required to achieve good crop performance and high yield production. Emphasis is given to the granary areas where there is a higher potential to achieve the set yield target. The aim of this study is to develop systematic approaches in location-specific fertilizer management for high-yield rice production within the granary areas. In order to satisfl the main objective of this study, two types of data namely primary and secondary data were collected, gathered, and compiled. Primary data was gathered from experimental studies that were conducted throughout granary areas. The data was analyzed and used to develop location-specific fertilizer management technology package, as well as for package verification studies. Secondary data was compiled from soil survey report and used to run the package for estimating fertilizer recommendation rate on large-scale operational basis. It was also used to estimate location-specific potential yield and to set practical yield target for various locations. The radiation potential yield of variety MR219 of granary areas was estimated using Rice Supply and Demand Analysis (RSDA) model. Based on the potential yield performance, the granary areas were broadly grouped into three cropping zones namely Northeastern, Northwestern, and Central Western Zones. Attainable yield as affected by radiation level and indigenous soil fertility status was estimated using CropEnvironment Resource Synthesis (CERES) Rice model. Variation of attainable yield is markedly represented by the Northeastern Zone that covers three granaries namely Kemubu Irrigation Scheme (KADA), Kemasin- Semerak Irrigation Scheme, and Besut Irrigation Scheme (KETARA). Thus in this study the Northeastern cropping zone was chosen to develop the attainable yield map. In modern farming where managers are exposed to advance technology and up to date facilities, location-specific computerized fertilizer recommendation tool can be handled easily. Development of computerized fertilizer-management technology tool (FERTO) for location-specific fertilizer recommendation was able to assist managers to improve crop yield performance and achleve set high-yield target. Verification result shows model under estimated of set yield target (10 tka) of about 9%. The package was also used to estimate the amount of fertilizer required by all granaries for two cropping seasons. Benefit cost ratio of about 2:l for the package could be achieved as compared to subsidy fertilizer of about 1.5: 1 only. However, generalization and simplification of the detail information for policy formulation is necessary. Using this approach, 14 reliable fertilizer management zones were identified. This information is useful in developing revised subsidy fertilizer scheme in order to achieve the set national average yield target of 7 tka.